Respon Pemberian Pupuk Kotoran Ayam dengan Arang Sekam Teradap Pertumbuhan Tanaman Nilam (Pogostemon Cablin Bent) di bawah Tegakan Tanaman Kayu Manis - Anis Tatik Maryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Patchouli (Pogostemon cablin, benth) is one of the leading national commodities in the form of Patchouli oil. Indonesia is a tropical country, has high potential in the production of Patchouli plants. In order to obtain high- quality patchouli plants and high production, it is necessary to fertilize the planting medium, using a mixture of chicken manure and rice husk charcoal as organic fertilizer can increase the growth of patchouli (Pogostemon cablin Bent). The purpose of this study was to find out, the dose of chicken manure mixed with rice husk charcoal which could provide the best growth of patchouli plants under stands of cinnamon plants. This study used a randomized block design (RBD) with 4 treatments and 6 replications so that 24 plants were obtained for each treatment. Polybag size 15 x 20 cm, with a distance between treatments of 1 meter. Parameters observed were number of leaves, plant height, total leaf area, herb production and essential oil content. The data collected was then analyzed using the DMRT advanced test. Supporting data in the form of initial soil analysis, analysis of a mixture of chicken manure and rice husk charcoal. Doses of a mixture of chicken manure and rice husk charcoal gave a significantly different effect on the growth of patchouli cuttings under cinnamon stands. The conclusion of this study is that the application of various doses of a mixture of Chicken Manure and Rice Husk Charcoal can increase patchouli plant growth, herb dry weight and essential oil content better. The best dosage recommendation is the administration of P1 treatment, namely 100 grams of Chicken Manure Fertilizer and 50 grams of Rice Husk Charcoal Focus 10.